A single multiplex PCR and SNaPshot minisequencing reaction of 42 SNPs to classify admixture populations into mitochondrial DNA haplogroups - Paneto, Greiciane G. [UNESP]; Koehnemann, Stephan; Martins, Joyce A. [UNESP]; Cicarelli, Regina Maria Barretto [UNESP]; Pfeiffer, Heidi (Elsevier B.V., 2011)
SNaPshot minisequencing reaction is in increasing use because of its fast detection of many polymorphisms in a single assay. In this work we described a highly sensitive single nucleotide polymorphisms (SNPs) typing method with detection of 42 mitochondrial DNA (mtDNA) SNPs in a single PCR and SNaPshot multiplex reaction, in order to allow haplogroup classification in Latin American admixture population. We validated the panel typing 160 Brazilian individuals. Complete SNP profiles were obtained from 10 pg of total DNA. We conclude that it is possible to build and genotype more than forty mtDNA SNPs in a single multiplex PCR and SNaPshot reaction, with sensitivity and reliability, resolving haplogroup classification in admixture populations. (C) 2010 Elsevier B.V. and Mitochondria Research Society. All rights reserved.
Keywords: Admixture populations; Brazil; Haplogroup affiliation; Mitochondrial DNA; SNaPshot reaction